Preliminary characterization and antioxidant and hypoglycemic activities in vivo of polysaccharides from Huidouba. Issue 12 (14th November 2018) - Chen, Juncheng; Li, Lin; Zhou, Xin; Sun, Pengyao; Li, Bing; Zhang, Xia
Abstract : Here, the antioxidant and hypoglycemic activities of polysaccharides from Huidouba were preliminarily characterized. Abstract : Here, the antioxidant and hypoglycemic activities of polysaccharides from Huidouba were preliminarily characterized. Two novel polysaccharides, HDBP-1 and HDBP-2 (127.33 kDa and 9.703 kDa, respectively), were purified by ultrafiltration using a Sephadex G-200 column and then characterized by high-performance gel permeation chromatography (HPGPC), high-performance liquid chromatography (HPLC), infrared spectroscopy (FT-IR), GC-MS, NMR and the Congo red test. HDBPs (crude Huidouba polysaccharide (CHDBP), HDBP-1 and HDBP-2) exhibited significant antioxidant and α-glucosidase inhibitory activities in vitro . In addition, in vivo hypoglycemia experiments in mice revealed that CHDBP, HDBP-1 and HDBP-2 demonstrated active roles in reversing diabetic symptoms. These polysaccharides decreased the serum triglyceride (TG), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C) levels and significantly improved oral glucose tolerance (OGT), indicating that HDBPs suppressed obesity and alleviated insulin resistance. Moreover, HDBP-2 with lower molecular weight performed better in antioxidant capacity, α-glucosidase-inhibiting activity and hypoglycemic activity. These results suggest that HDBPs have the potential to be functional foods with hypoglycemic properties.